Understanding the Effect of Health Consciousness and Perceived Risk on Intention to Consume Herbal Product Moderated by Trust Belief - Widyaningtyas, Dian (International Review of Management and Marketing, 2026)
The growing trends in the use of herbal products has increased following COVID-19. People are opting for a healthier lifestyle, as the emergence of health disorders which encourages them to strengthen their immune systems. This study aims to investigate the role of health consciousness, perceived risk, and trust belief in consumer behaviour amidst the widespread concern about the safety of herbal products. Using purposive sampling, this study involved 357 respondents, 43% men and 57% women. Data processing of the structural model was performed using Smart PLS 3.0. SEM-PLS was chosen because it allows for the simultaneous measurement of latent variables and the examination of structural relationships within a complex model. The empirical results show that health consciousness and trust belief have a positive and significant effect on the intention to use the product. Meanwhile, Perceived risk fails to influence intention because consumers believe herbal benefits outweigh potential risks, which can be further minimized by choosing standardized products. Moreover, trust belief reduces the gap between perceived health benefits and perceived safety. This study demonstrated that the Theory of Planned Behaviour can be used effectively to explain health-related behaviour. In practice, the herbal industry cannot simply promote health benefits; it must actively foster consumer trust belief by transparent product information.